REKONTRUKSI HUKUM PERJANJIAN PINJAMAN ONLINE ( PINJOL ) TERHADAP PROBLEMATIKAN PINJAMAN ONLINE - Sa'adah, Nur; Ari Widiarti (Rechtsregel : Jurnal Ilmu Hukum, 2025)
Financial technology is a term used to describe these technology-based financial services. Some examples of fintech, such as online loans and peer-to-peer lending, offer easier and more flexible loan terms and conditions compared to conventional financial institutions like banks. Furthermore, online loan terms can be tailored to your needs. Risks of breach include personal data theft, high interest rates, and unilateral collection. This is highly likely and can impact customers of these online lending companies. Consequently, many customers who use these online lending services face problems. For example, they may be unable to pay their bills because the interest is too high or the term is too short. This research aims to address and describe the legal construction of online loan agreements (pinjol) according to applicable laws and regulations in Indonesia, as well as the legal certainty and fairness for online loans according to applicable laws and regulations in Indonesia. This research is socio-legal research, which views law as an empirical social phenomenon. This research is descriptive, gathering information regarding the status of a variable or theme, a phenomenon, or an existing condition, namely the condition of the symptom as it was at the time of the research. In an effort to protect consumers who use financial services, the OJK continues to intensively implement its programs based on Article 28 letter (a) of Law Number 21 of 2022 concerning the OJK, which explains that to protect consumers and the public, the OJK is authorized to take preventive measures against consumer and public losses, one of which is providing information and education to the public regarding the characteristics of the financial services sector, its services and products.